O mar ensina: Avaliação da política de expansão do IFCE junto aos povos do mar de Camocim/CE - Brilhante, Aniely Silva (2020)
This work aims to evaluate the public policy of expanding professional and technological education, within the scope of the Federal Institute of Education, Science and Technology of Ceará (IFCE), and its relationship with the development of the “peoples of the sea”, located in the municipality of Camocim/CE. This is a qualitative assessment, to be carried out through a case study at the IFCE campus Camocim with the “people of the sea” in the Praia de Camocim neighborhood. To this end, it presents itself as a central question: to what extent the IFCE's expansion policy has been contributing to the development of the “peoples of the sea” of Camocim / CE? This question is based on the theoretical discussion on the concept of development in Celso Furtado (1980) and the discussion of the concept of professional education in Saviani (2007), among others. The theoretical-methodological perspective of the adopted evaluation presents Lejano's (2012) experiential analysis as parameters, which seeks to base the evaluative research on the relationship between text and policy context. In a complementary way, the studies of “in-depth evaluation” by Rodrigues (2008), Gussi (2016) and Gonçalves (2008) are used. The methodological path consisted of three stages: bibliographic, documentary and statistical research; field research with observation in Bairro Praia and individual interviews and, finally, the organization and analysis of data. The central subjects of the research were the fishermen, students of IFCE, belonging to the peoples of the sea, teachers, administrative technicians, collaborators and manager of the Camocim campus. In this way, it carried out the development of the analytical axes of in-depth evaluation (RODRIGUES, 2008), namely: (i) the analysis of the Brazilian political context of the Lula and Dilma Government; (ii) the analysis of the content of the expansion policy of the Federal Institutes; and (iii) the construction of the institutional trajectory of the IFCE campus Camocim. Finally, the assessment centered the experience of IFCE's expansion policy on its relationship with the “people of the sea” in Camocim, establishing parameters for the relationship between the policy text and the local context of its implementation (LEJANO, 2012). As a result, it is evaluated that the expansion of the IF provides access to public, face-to-face and federal education and that the IFCE campus Camocim contributes to the change of life of the family of the fishermen. However, the dialogue with the peoples of the sea is institutionally embryonic, although with the potential to advance in the face of the possibility of IFCE in revising its pedagogical methods in terms of an emancipatory professional education, and being consistent with the context of the local community. to achieve development in the sense of Furtado (1980). In this sense, it is suggested to incorporate more inclusive and flexible methodologies through an institutional project articulated with teaching, research and extension, respecting the autonomy of the subjects and the community of the “peoples of the sea”.